The Works and Thoughts of Rahmah El-Yunusiyah as "Bundo Kanduang": Towards Modernity in Women Education Within an Islamic Education Perspective - Yusutria Yusutria; Zalik Nuryana; Charles Charles; Abdul Hopid; Yuherman Yuherman; Rina Febriana (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Women’s disparities and injustices in obtaining adequate education become the background of Rahmah El-Yunusiyah to modernize women’s education. This is a library study that uses a historical approach. The data were obtained from various references through a documentation method, and the collection technique used was accumulating, analyzing, and selecting as the goal. Once the source was identified, the descriptive-analytical analysis was carried out using historical reinterpretation; therefore, all data are collected, reduced, analyzed, and concluded. Rahmah el-Yunusiyyah is an independent warrior and woman educator who has built many women education institutions dedicated to upholding women’s dignity in all aspects of life. The blend of curriculum among religion, Arabic, and general science is known as tripartite education. The teaching system is classical with a boarding system and provides three certificates.